Die missionêre uitdaging van die arbeidslewe - J.J. Kritzinger (Acta Theologica)
This article takes as its point of departure the observation that the church and its theology is largely geared (only) to the residential world. The churches function wherever their members are living and are spending their free (non-working, weekend) time. Even when there is a drive to reach other people, the orientation is likewise geographical. Church is for Sundays. Meanwhile there is an unreached weekday world of economy, politics, labour and finance. People spend the majority of their waking hours working, or longing to work. Not only should the gospel penetrate the whole of reality, but the fact is that this world of work is shaping also the home world. Some aspects of this unfinished task are indicated for the South African church.